(untitled) (The International Journal for Scientific Research, 2025)
This research aims to examine the legal and regulatory framework for protecting personal data in the context of its increasing use by companies, institutions, and individuals, especially in light of the technological boom and global digital transformation. The study focuses on analyzing prominent international standards, most notably the General Data Protection Regulation (GDPR) issued by the European Union, in addition to the research also addresses aspects related to private international law, particularly the legal challenges arising from the transfer of data across national borders and the conflicting laws between countries, which pose complex legal issues that require effective international coordination. The research also examines the responsibilities of companies and organizations in adopting strict privacy protection policies and ensuring the security of the data they collect and process, as well as the role of individuals in protecting their personal data. The study concluded that personal data protection is no longer a purely domestic issue, but rather a global one that requires integration between national laws and international standards, as well as international cooperation to ensure effective and comprehensive protection in a constantly changing, cross-border digital environment.